ETMR-09. THE ROLE OF RADIATION FOR EMBRYONAL TUMOR WITH MULTILAYERED ROSETTES - Kondo, Akihide (Neuro Oncol, 2020)
BACKGROUND: Embryonal tumor with multilayered rosettes (ETMR) is a challenging tumor. The prognosis of the patients suffering from this tumor is extremely poor. We have survival cases of more than 12 months. However, the status of illness is different. In order to clarify the cause of this difference, we reviewed our treatments in this study. TREATMENT COURSE: We have two cases. Both have relapsed after the same chemotherapy after the same radiation therapy. After the recurrence we used protocols that were included extended resection, second radiation therapy with bevacizumab. METHODS: We compared molecular biological evaluations for the initial and recurrent tumors. The resection rate at the time of second removal and the intensity of radiation therapy intensity were compared. RESULTS: We succeeded to remove the tumors with the confirmation of intraoperative MRI. No apparent differences could be seen in molecular biological characters of tumors before and after treatment. There was a difference between the period until radiation therapy and the irradiation methods. CONCLUSIONS: This tumor is untreatable only by resection. We need the second radiation therapy with bevacizumab. It was presumed that tumor should be irradiated quickly with appropriate irradiation field and dose.